Children in sustainable and responsible tourism - Séraphin, Hugues (Emerald Publishing Limited, 2022)
Sustainability has become a core concept in considering tourism planning and development. Existing literature on sustainable tourism suggests that tourism will become more sustainable if all stakeholders participate in the tourism development process. Children in Sustainable and Responsible Tourism seeks to fill an absence of research in the sustainable and responsible tourism field involving children as stakeholders. Children in Sustainable and Responsible Tourism argues that children's empowerment should be a core component of any responsible tourism initiatives, and that children's involvement and support should be a requirement in helping to achieve the Sustainable Development Goals (SDGs). Hugues Séraphin's ground-breaking study directly addresses the issue that academic researchers and industry practitioners alike have overlooked and under evaluated the significance of this key segment for the industry. Chapters address issues related to both the 'why' and 'how' of empowering children to be responsible tourists and potential future industry practitioners while providing recommendations for current industry professionals.